2019
DOI: 10.1161/strokeaha.118.024143
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and Brain Magnetic Resonance Imaging Abnormalities

Abstract: Background and Purpose— Atrial fibrillation (AF) is associated with dementia independent of clinical stroke. The mechanisms underlying this association remain unclear. In a community-based cohort, the ARIC study (Atherosclerosis Risk in Communities), we evaluated (1) the longitudinal association of incident AF and (2) the cross-sectional association of prevalent AF with brain magnetic resonance imaging (MRI) abnormalities. Methods— The longitudinal anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Our finding that the association between AF and WMHs disappeared after taking stroke and cardiovascular risk factors into account is in line with results from the Mayo Clinic Study of Aging 29 and the Atherosclerosis Risk in Communities Neurocognitive Study. 30 , 31 In addition, our finding that AF was not associated with WMHs in individuals without a history of stroke is in line with the Framingham offspring study 32 and the German AF Competence NETwork Study. 33 However, in our study, individuals with both AF and anticoagulant treatment had larger WMH volumes than individuals without AF after adjustments, including cardiovascular risk factors, heart disease, and symptomatic stroke, while individuals with AF but no anticoagulant treatment did not have larger WMH volumes than individuals without AF.…”
Section: Discussionsupporting
confidence: 86%
“…Our finding that the association between AF and WMHs disappeared after taking stroke and cardiovascular risk factors into account is in line with results from the Mayo Clinic Study of Aging 29 and the Atherosclerosis Risk in Communities Neurocognitive Study. 30 , 31 In addition, our finding that AF was not associated with WMHs in individuals without a history of stroke is in line with the Framingham offspring study 32 and the German AF Competence NETwork Study. 33 However, in our study, individuals with both AF and anticoagulant treatment had larger WMH volumes than individuals without AF after adjustments, including cardiovascular risk factors, heart disease, and symptomatic stroke, while individuals with AF but no anticoagulant treatment did not have larger WMH volumes than individuals without AF.…”
Section: Discussionsupporting
confidence: 86%
“…Incident AF is associated with structural changes in brain MRI, including worsened sulcal grade, larger ventricles, and subclinical cerebral infarctions. However, analyses from the ARIC and the Framingham Heart Study could not demonstrate any association between AF and WMHs or total brain volume after adjustment for vascular risk factors [ 39 , 47 , 49 ]. Notably, WMHs, attributed to small vessel disease and global cerebral hypoperfusion, were not associated with AF [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain MRI was performed in participants of the ARIC study, where, according to a longitudinal analysis, those (3%) who developed AF (29/963 participants) had higher odds of increase in subclinical cerebral infarctions (OR: 3.08, 95% CI: 1.39-6.83), worsening sulcal grade (OR: 3.56, 95% CI: 1.04-12.2), and worsening ventricular grade (OR: 9.34, 95% CI: 1.24-70.2). 103 In cross-sectional analysis, those with AF (35/969 participants, 3.6%) had greater odds of higher sulcal (OR: 3.9, 95% CI: 1.7-9.1) and ventricular grade (OR: 2.4, 95% CI: 1.0-5.7) after multivariable adjustment and no difference in WMH or total brain volume. The authors concluded that AF is independently associated with higher subclinical cerebral infarctions and worsening sulcal and ventricular grade morphological changes associated with aging and dementia.…”
Section: Brain Imagingmentioning
confidence: 91%